2016
DOI: 10.1002/jcsm.12108
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunction of respiratory muscles in critically ill patients on the intensive care unit

Abstract: Muscular weakness and muscle wasting may often be observed in critically ill patients on intensive care units (ICUs) and may present as failure to wean from mechanical ventilation. Importantly, mounting data demonstrate that mechanical ventilation itself may induce progressive dysfunction of the main respiratory muscle, i.e. the diaphragm. The respective condition was termed ‘ventilator‐induced diaphragmatic dysfunction’ (VIDD) and should be distinguished from peripheral muscular weakness as observed in ‘ICU‐a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
82
0
10

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 97 publications
(94 citation statements)
references
References 141 publications
(348 reference statements)
2
82
0
10
Order By: Relevance
“…Preclinical models of MV provide important information regarding the signalling pathways required for VIDD. The rat model of MV is clinically significant because it greatly mimics the diaphragm weakness observed in mechanically ventilated patients, including during conditions where diaphragm weakness may be exacerbated as a result of ICU‐acquired comorbidities (i.e. sepsis) .…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical models of MV provide important information regarding the signalling pathways required for VIDD. The rat model of MV is clinically significant because it greatly mimics the diaphragm weakness observed in mechanically ventilated patients, including during conditions where diaphragm weakness may be exacerbated as a result of ICU‐acquired comorbidities (i.e. sepsis) .…”
Section: Discussionmentioning
confidence: 99%
“…Under acute inflammation such as sepsis, the presence of muscular weakness including the dysfunction of respiratory muscles has been reported in animal models and patients . Under these conditions, the pathophysiology of muscle weakness such as proteolysis has been elucidated to a large extent using animal models .…”
Section: Discussionmentioning
confidence: 99%
“…30 The human skeletal muscle proteome project is currently underway to characterize muscle proteins and the way they change during ageing and disease. 36 Cheung et al recently reported that testosterone deprivation selectively decreases lower limb muscle function, predominantly affecting muscles that support body weight and muscles that accelerate the body forward during walking and mediate balance. 33 Anorexia is likewise very prevalent in patients with HF as assessed using a 6-point Likert scale.…”
Section: Screening and Diagnosing Sarcopeniamentioning
confidence: 99%